2016
DOI: 10.1007/s10832-016-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen partial pressure on co-firing behavior and magnetic properties of LTCC modules with integrated NiCuZn ferrite layers

Abstract: low-κ dielectric LTCC was developed, to realize successful co-firing with NiCuZn ferrite tapes. A critical high-temperature process in the production of highly integrated LTCC modules is the migration of silver from inner conductors into the LTCC glass phase. Intensive silver migration causes strong deformation of LTCC multilayers during firing in air. Silver migration into the LTCC glass phase depends on oxygen content of the sintering atmosphere and can be minimized by sintering in nitrogen atmosphere. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The occurrence of Ag diffusion in ferrite multilayers cofired with Ag paste in air has been observed frequently 4 . Cofiring at lower oxygen partial pressure was proposed as one option to prevent silver diffusion into surrounding low‐ k dielectric and ferrite layers 30 . The room‐temperature inductance and quality factor of a multilayer inductor fabricated by cofiring Ni 0.40 Cu 0.20 Zn 0.42 Fe 1.98 O 3.99 without sintering additive and AgPd at 900°C are shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of Ag diffusion in ferrite multilayers cofired with Ag paste in air has been observed frequently 4 . Cofiring at lower oxygen partial pressure was proposed as one option to prevent silver diffusion into surrounding low‐ k dielectric and ferrite layers 30 . The room‐temperature inductance and quality factor of a multilayer inductor fabricated by cofiring Ni 0.40 Cu 0.20 Zn 0.42 Fe 1.98 O 3.99 without sintering additive and AgPd at 900°C are shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…The segregation of CuO-rich phase at grain boundary for NiCuZn ferrites strongly depends on the sintering atmosphere [36,37]. Naghib zadeh et al [36] reported that partial decomposition of NiCuZn ferrites to form nonmagnetic cuprous oxide that hinders magnetic exchange between ferrite grains and hence resulting in a reduction of permeability as shown in Fig. 19.…”
Section: Multilayer Nicuzn Ferrite Power Inductorsmentioning
confidence: 99%
“…These result in the interlayer misalignment between the printed patterns and via holes. Therefore, it is generally understood that the manufacture of large-area multilayer ceramic substrate is not practical unless the shrinkage tolerance can be reduced below the [36]. Copyright@2016, Springer levels normally attributed to free sintering.…”
Section: Multilayer Nicuzn Ferrite Power Inductorsmentioning
confidence: 99%